2011
DOI: 10.1007/s00431-011-1609-0
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary ultrastructural abnormalities in Mycoplasma pneumoniae pneumonia in 22 pediatric patients

Abstract: Mycoplasma pneumoniae pneumonia (MPP) is characterized by ciliary ultrastructural abnormalities that cause abnormal mucociliary function leading to refractory or persistent pneumonia. Herein, we analyzed ciliary ultrastructural defects in 22 children with MPP and determined the association of these defects with prognosis. Ciliary ultrastructural abnormalities occurred in all patients. Ciliated cells with loss of cilia occurred in 15. Cytoplasmic blebbing occurred in eight. Ambiguity of the "9 + 2" microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In our study, we found that the presence of mucus plugs was associated with longer time to radiographic clearance in patients with RMPP. Liang and her colleagues8 found that M. pneumoniae pneumonia with severe cilia abnormalities was associated with longer time to radiographic clearance, but they did not focus on analysis of the mucus plugs in the bronchoscopic findings. Mucus plug formation was actually a manifestation of severe cilia abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the presence of mucus plugs was associated with longer time to radiographic clearance in patients with RMPP. Liang and her colleagues8 found that M. pneumoniae pneumonia with severe cilia abnormalities was associated with longer time to radiographic clearance, but they did not focus on analysis of the mucus plugs in the bronchoscopic findings. Mucus plug formation was actually a manifestation of severe cilia abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive inflammation reaction may lead to the immune disorder, which might be related to the severity of RMPP in children. Previous studies revealed that strong cellular immunological responses cause severe cilia abnormalities in RMPP1213. Severe cilia abnormalities reduce the immune function of the airways and disrupt mucociliary clearance, thereby causing the mucous plugs that are responsible for the development of large infiltrations or atelectasis on chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of BALF collection has been described elsewhere. [ 27 ] The bronchoscopy imaging and the MP detection in BALF were done 2 to 7 days postadmission; all other variables were routinely collected within 24 hours of admission.…”
Section: Methodsmentioning
confidence: 99%